O papel dos movimentos sociais das pessoas com deficiência na efetivação de políticas educacionais de acesso ao ensino superior na UNIOESTE - Padua, Ivã José de (2018)
The present paper deals with the creation of the Institutional Program of actions related to people with special needs (PEE) of UNIOESTE and its relationship with social movements. We have as main objective to analyze the contribution of the organized social movements of people with disabilities to the admission and permanence of these subjects in higher education, through the study of actions implemented in the PEE. Therefore, we carried out documentary and bibliographic research that enabled us to understand the contribution of social movements in the creation of the PEE. The research is structured in three sections. In the first one, we analyze historical aspects of the different modes of production. In the primitive world, practices of natural selection prevailed; in the slave mode production, practices of extermination or abandonment; in the feudal production mode, dominated by the church, practices of charity and philanthropy advanced, and in the mode of capitalist production, we discuss the great changes in the logic of production, with a new economic order based on social exclusion. In the second section of the research, we analyze the social movements with the dominance of the capitalist mode of production, pointing out the possible advances and its limits for the reproduction of the current productive societal order. We also organized a history of the Brazilian education of people with disabilities, in order to better understand the social movements of these subjects. Subsequently, we researched the association of organized movements of people with disabilities, and then analyzed the history of ACADEVI and its contribution in defense of the rights of visual impairment people in Cascavel. We also discussed the history of the constitution of the municipal forum in defense of the rights of people with disabilities and the difficulties to maintain and expand the rights of this segment. In the third section, we study the history of the struggles to create and consolidate UNIOESTE, and, in the midst of these struggles, we came to the creation of the PEE. We can affirm that the social movements of people with disabilities played a decisive role in the creation and institutionalization of the institution